Relationship between infertility and psychiatric disorders - Ostrowska, Sandra; Stróżna, Małgorzata; Alekso, Ivan; Chil, Piotr Arkadiusz; Pyziołek, Marta; Brzezińska, Wiktoria; Kowalczyk, Klaudia (Journal of Education, Health and Sport, 2025)
Introduction: Infertility is a serious health issue which affects milions of couples on the world. The dynamics of partnerships and social functioning, the effect of infertility on people's mental health, with a focus on family and gender disparities, are some of the most thorough literature evaluations. Methods: This review was based on about 63 scientific publications from the last years including meta-analyses, original works and systematic reviews. The most important topics discussed: various mental disorders related to infertility and their consequences, partner relationships, impact of treatment, social and family functioning. Conclusions: There is a clear correlation between infertility and increased psychological distress, specifically stress, anxiety, and depression symptoms. The length of infertility and the failure of reproductive therapies can cause the emotional strain to increase. Because long-term stress, worry, and depression can interfere with menstrual cycles, hormone control, and sexual function, psychiatric illnesses may also be a contributing factor to infertility. Assisted reproductive technologies [ART] can be a source of psychological stress as well as hope. The emotional fluctuations linked to ART highlight the necessity of ongoing psychological care during the course of treatment. Key words: infertility, psychiatric disorders, mental health, reproductive treatment, depression, anxiety, eating disorders, obsessive-compulsive symptoms